2010
DOI: 10.5767/anurs.cmat.100102.en.151p
|View full text |Cite
|
Sign up to set email alerts
|

Determining Optimum Tilt Angles and Orientations of Photovoltaic Panels in Niš, Serbia

Abstract: Performance of photovoltaic (PV) solar module is affected by its orientation and its tilt angle with horizontal plane. These two parameters change the amount of solar energy received by the surface of the PV module. In this experiment the rotational solar module was positioned in the predefined angles. In these positions the values of current, voltage, power and solar radiation intensity were measured. The optimum positions were determined as positions in which maximum values of solar intensity and maximum pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…The opening of the PV panel angle with the horizontal depends on the latitude. Different optimized tilt angles can be calculated for each geographical coordinate [7]. Moreover, for choosing the right position of the PV the climate conditions such as clearness of the sky play an important role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The opening of the PV panel angle with the horizontal depends on the latitude. Different optimized tilt angles can be calculated for each geographical coordinate [7]. Moreover, for choosing the right position of the PV the climate conditions such as clearness of the sky play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature provides many examples of simple ways to determine the optimum tilt angle for PV panels installation as a function of latitude [1], [2]. The mathematical models with multiple variables are reduced at formulas like β=φ [3], [4] β∈[φ,φ+20°] [5], β=φ+15° [6] β=φ+10° [2], β=φ-13 [7] for PV panels with one axis. Another approach is using two values for the tilt angle, one for summer and the other one for winter, such as β=φ±8° [8], β=φ±5° [9], β=φ±15° [3], for PV panels with double axis, where β is for the tilt angle, φ is the latitude numerical value, "+" is for winter, and "−" is for summer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in 2013, Jafarkazemi and Saadabadi [14] found that the optimum orientation for Abu Dhabi was due south. Also, in 2010, Pavlović, et al [15] estimated the optimum orientation for Serbia to be due south. Finally, in 2018, Omar and Mahmoud [16] confirmed that the optimum orientation for Palestine is due south.…”
Section: Solar Anglesmentioning
confidence: 99%
“…The resulting main error sources are hence systematic and high precision, accuracy and resolutions can therefore be obtained even when relatively simple control laws are used. Owing to these advantages, in addition to the mentioned technological fields, compliant mechanisms are thus widely used also in mechanical engineering design, metrology and scientific instrumentation, information & communications technology (ICT), aerospace and astrophysics, machine tools, robotics or biomedical applications (National Physical Laboratory 1956;Jones 1962;Smith and Chetwynd 1992;Smith 2000;Yin and Ananthasuresh 2003;De Bona and Zelenika 2006;Howell 2010;Pavlović and Pavlović 2013;Bhattacharya, Bepari, and Bhaumik 2014;Ivanov and Corves 2014;Khan and Ananthasuresh 2014).…”
Section: Introductionmentioning
confidence: 99%